A new species of Philoscirtus (Orthoptera: Phaneropteridae: Mecopodinae) from the West Usambara Mountains of Tanzania and its conservation status - Hemp, Claudia; Heller, Klaus-Gerhard; Warchałowska-Śliwa, Elżbieta; Hemp, Andreas (Zootaxa, 2015)
A new Philoscirtus species, P. viridulus n. sp. from forests of the West Usambara Mountains is described and the genus revised. Both species of the genus are known from few localities only. Their habitats are under pressure due to an increasing human population in the East and West Usambara Mountains. Both taxa should be included thus in the IUCN red list of globally threatened taxa to attract more attention to the importance of small forest patches. The biogeographical distribution of species from West Usambaran forests is discussed indicating on one hand that there must have been isolating mechanisms within the West Usambara Mountains and that part of the observed biodiversity in flightless Orthoptera is due to speciation processes not older than approximately 2 million years.